Biaxial testing system for characterization of mechanical and rupture properties of small samples. (October 2022) - Corti, Andrea; Shameen, Tariq; Sharma, Shivang; De Paolis, Annalisa; Cardoso, Luis
Graphical abstract: Abstract: The study of damage and rupture of soft tissues using a tensile testing system is essential to understand the limits of mechanical behavior and loss of function in diseased tissues. However, commercial material testing systems are often expensive and may not be fully suitable for rupture tests of small samples. While several research laboratories have developed custom, less expensive, uniaxial or biaxial devices, there is a need for an open source, inexpensive, accurate and easy to customize biaxial material testing system to perform rupture tests in small soft samples. We designed a testing system (BiMaTS) that (a) was shown able to perform uniaxial and biaxial tests, (b) offers a large travel range for rupture tests of small samples, (c) maintains a centered field of view for effective strain mapping using digital image correlation, (d) provides a controlled temperature environment, (e) utilize many off-the-shelve components for easy manufacture and customization, and it is cost effective (∼$15 K). The instrument performance was characterized using 80%-scaled down, ASTM D412-C shaped PDMS samples. Our results demonstrate the ability of this open source, customizable, low-cost, biaxial materials testing system to successfully characterize the mechanical and rupture properties of small samples with high repeatability and accuracy.